(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The present article reveals the possibility of studying the awareness of teachers of various types of schools (special, integrated, mass), students and undergraduates of pedagogical universities (future teachers) in the issues under consideration, particularly, related to the formation and development of geometric conceptions and definitions in children with visual impairments. The success of this study depends on the level of awareness of teachers of mentioned schools, students and undergraduates of pedagogical universities about the peculiarities of the development of those children, the means, methods and conditions for their application to address these issues. It is known, that visual impairment significantly complicates the playing, physical, cognitive, educational, labor and other types of activities of those children. Blind and visually impaired students are characterized by passivity, introversion, insufficient activity. Therefore, the study of many aspects of the considered problem and the development of approaches to the development of the level of awareness of teachers, students and undergraduates of pedagogical universities in the issues under consideration, particularly, related to the formation and development of geometric ideas and concepts in children with visual impairments and the development of approaches to expanding the level of awareness in these issues will serve as the basis for improving the formulation of this work in the types of schools under consideration. In the special scientific and methodological literature, the importance of studying this problem is emphasized; however, it is insufficiently developed in theoretical and practical aspects that in its turn defines the relevance of this study, its theoretical and practical significance.